2021
DOI: 10.3390/ma14247671
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Tribological Assessment of Biomedical 316 Stainless Steel Subjected to Pulsed-Plasma Surface Modification: Comparison of LPBF 3D Printing and Conventional Fabrication

Abstract: The structural features and nanoindentation/tribological properties of 316 stainless steel fabricated by conventional rolling and laser-based powder bed fusion (LPBF) were comparatively investigated regarding the effect of surface-pulsed plasma treatment (PPT). PPT was performed using an electrothermal axial plasma accelerator under a discharge voltage of 4.5 kV and a pulse duration of 1 ms. Optical microscopy, scanning electron microscopy, X-ray diffraction, nanoindentation measurements and tribological tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…For all the austenitizing temperatures a sharp rising of SHR at the initial strain stage (=0.005−0.01) was followed by a decrease in the SHR value at up to 0.025, which is attributed to the cumulative interactions of gliding dislocations followed by the blocking of the close-packed plains of their gliding [59,60]. The next strain stage was characterized by an increase in the SHR, indicating a strain hardening phenomenon [61]. It is observed that the SHR curves for TA=770 °C and TA=830 °C exhibited similar behavior, with a minor hardening effect lasting up to the strain of about 0.05.…”
Section: Discussionmentioning
confidence: 92%
“…For all the austenitizing temperatures a sharp rising of SHR at the initial strain stage (=0.005−0.01) was followed by a decrease in the SHR value at up to 0.025, which is attributed to the cumulative interactions of gliding dislocations followed by the blocking of the close-packed plains of their gliding [59,60]. The next strain stage was characterized by an increase in the SHR, indicating a strain hardening phenomenon [61]. It is observed that the SHR curves for TA=770 °C and TA=830 °C exhibited similar behavior, with a minor hardening effect lasting up to the strain of about 0.05.…”
Section: Discussionmentioning
confidence: 92%
“…the (Nb,V)C carbide precipitation. As shown in Figure 5h, the formed precipitates interacted with dislocations using the Orowan mechanism in the grains, preferably oriented relative to the deformation direction, forming a dislocation "forest" that contributed to the steel strength [49,50]. The application of AC just after HR changed the structure significantly.…”
Section: Microstructure Characterizationmentioning
confidence: 97%
“…A comparison of the structures of TMCP and NR specimens showed the latter had no nano-particles and allowed to the presumption that the progressive accumulation of crystal defects due to a lower FRT under TMCP facilitated the (Nb,V)C carbide precipitation. As shown in Figure 5h, the formed precipitates interacted with dislocations using the Orowan mechanism in the grains, preferably oriented relative to the deformation direction, forming a dislocation "forest" that contributed to the steel strength [49,50]. the (Nb,V)C carbide precipitation.…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…In metallic materials, maximum nanoscale depth can reach up to 0.2 microns, which is beneficial for assessing the mechanical properties of thin films and coatings [ 20 , 21 , 22 ]. On the other hand, nIIT has been successfully utilized, with specific reference to SS 316L, to inspect the effects of surface modifications, such as those induced by irradiation [ 23 ], pulsed plasma [ 24 ], nitriding [ 25 ], sol-gel thin coating [ 26 ], and more. To the best of the authors’ knowledge, no studies, except for the one published by [ 27 ] on the fatigue behavior of PBF-LB SS 316L under different orientations (vertically, horizontally and at a 45° angle) using Vickers instrumented macro-indentation, have been conducted on the elastoplastic behavior of either SS 316L steel or its PBF-LB counterpart.…”
Section: Introductionmentioning
confidence: 99%